Peran Perempuan Madura dalam Membangun Keluarga Sakinah Mawaddah Warahmah (Studi terhadap Ibu Nyai Karier Pondok Pesantren di Bangkalan) - Rajaby, Imadudin; Hipni, Muhammad (Civiliza Publishing, Indonesia., 2023)
Madurese society considers women as family members who need to be looked after, cared for, and are seen as a symbol of men's struggle to maintain their dignity in society. Therefore, women are placed in an environment that is considered sacred and separate from men's territory. Their belief that work is charity and has the ability to form independence has become part of the individual's ethos since their education in the nuclear family. The aim of this research is to understand the role of Madurese women in building the Sakinah Mawaddah Warahmah family, especially in the Islamic boarding school environment in Bangkalan. The research method chosen was descriptive qualitative, chosen because it was considered very suitable for conducting a detailed review of the application of the rules. Data sources were obtained through searching scientific literature which included various field reviews related to the discussion material. This is interesting because the research focuses on the role of Mrs. Nyai who has a career in building the Sakinah Mawaddah Warahmah family. That way, we laypeople can take an example from him. Because many Madurese women have opened their minds to having a career, this research can be used as a reference.